Comparison of risk factors of cardiovascular disease among pre and postmenopausal women - Piskorz, Anna (2013)
Introduction: After menopause, mortality rate in women increases significantly. This trend may result not only from the changes in concentrations of reproductive hormones. Other factors, associated with lifestyle, may also play a great role. Objective: The purpose of this study is to assess and compare the occurrence of atherosclerosis risk factors and cardiovascular disorders in women before and after menopause. Materials and methods: The study involved 219 women, residents of Krakow, aged 30-65, in whom any previous CVD diagnosis or diabetes were excluded. Two main groups of women were distinguished: premenopausal (K1, n=113) and postmenopausal (K2, n=l06). The second one was subdivided into the natural menopause (K2a, n=88 ) and surgery related menopause (K2b, n=18) groups. The research focused on the evaluation of the occurrence of the CVD risk factors. Results: Postmenopausal women had a significantly higher BMI (p=0.000), WHR and WC as compared to premenopausal women. In comparison to premenopausal women (K1), women of the K2 group had significantly higher values of total cholesterol (p=0.000), glucose (p=0.04 ), CRP (p=O,0 128); Iower parameters of the antioxidant potential (FRAP, p=0.003, catalase p=0.023). Postmenopausal women significantly more often suffered from the depressive (p=0.005), metabolic syndrome (p< 0.001) and an increased (>= 5%) SCORE risk of a
Keywords: menopause; women; risk factors; cardiovascular disease